Social financing and the sustainability of social enterprises in Zimbabwe - Thabani Dundu; Dingilizwe Nkomo; Velmah Letani Sakala (Journal of Research and Innovation for Sustainable Society, 2023)
. Social enterprises are important contributors in boosting economic growth, creating jobs, and improving the quality of life for both entrepreneurs and the communities where they operate. The challenge facing most social entrepreneurs is the access to finance. This research aimed at developing an innovative financing model that best suit social enterprises in Zimbabwe. This was achieved by looking at the factors affecting sustainability of social enterprises and the challenges and opportunities for sustainable social financing in Zimbabwe. Using quantitative methodology, data was collected through close ended questionnaires that were distributed to social entrepreneurship stakeholders in Harare, Zimbabwe. Analysis of the quantitative data used the SPPSS 22 statistical software package. The key study findings identified the following six factors that directly impact the sustainability of social enterprises, that is, social finance access, government support, community attitude and involvement, governance, strategy and management skills and ability of entrepreneurs to solve complex problems. The main conclusions were that the lack of financial resources had most significant impact on the demand and supply of social entrepreneurship funds. The study recommends that, a revolving social innovation fund should be established to provide funding for social enterprises. This acts as suitable product on the supply side which social enterprises require. As a result, policymakers and stakeholders can come together to ease the process for social enterprises to acquire financing.